Exterior view of the eastern Garbhagriha of the Mahakal Temple - Temples of India Project Team (Jio Institute, 2024)
Similar to the southern garbhagriha (sanctum sanctorum) of the Mahakal Temple, the eastern garbhagriha also features a vedibandha (basal mouldings), jangha (wall) and shikhara (superstructure) in shekhari style. The vedibandha includes khura (hoof), kapotapalika (cyma recta), kumbha (pot), and kalasha (pitcher) mouldings. While the jangha remains entirely plain without any sculptural embellishments, the shikhara of the garbhagriha displays divine figures.